Sobre prácticas profesionales: notas teóricas y propuesta de modelización en el campo de infancia y familia = Professional practices: notes and theoretical modeling proposed in the field of child and family - Martino Bermúdez, Mónica Solange de; Espasandín Cárdenas, Cecilia (Textos & Contextos (Porto Alegre))
This paper, supported by the research project, Social Work with Families in the socio – legal field, seeks to explain the problems arising from the shaping of the professional practice. Based on the Sartrean approach on the dialectic of the objective and subjective, are ordered, for the purposes of discussion and analysis, certain types of practice found in the socio-legal field on family. The findings demonstrate the need for a thorough review of the profession to itself, which is still a must in the Uruguayan Social Work